Simple Culture Methods and Treatment to Study Hormonal Regulation of Ovule Development - Li, Bu-Fan; Yu, Shi-Xia; Hu, Li-Qin; Zhang, Yan-Jie; Zhai, Ning; Xu, Lin; Lin, Wen-Hui (Frontiers in Plant Science, 2018)
Ovule development is one of the most important processes in the reproductive development of higher plants and is a determinant of seed quality and quantity. Phytohormones play key roles in this process since loss-of-function mutants in hormone signaling show defective ovule phenotypes and reduced fertility. However, it is difficult to distinguish the direct effects of hormones on ovule development because it is parts of reproductive development and the defective phenotypes would be the indirect effects following the defective vegetative development. The treatment of hormones is a direct method to investigate the hormonal regulation of ovule development, but ovule is embedded inside several layers of floral organs, and traditional methods for hormone (or inhibitor) treatments have various limitations. We have developed simple methods to apply treatments to the flowers in a living plant, where an inflorescence apex is immersed into a solution in an inverted tube. We have also developed a specific system to culture and treat excised flowers/pistils. These procedures will be useful for research on the hormonal regulation of ovule development. We provide examples of how treatments with brassinosteroids (BR) and BR biosynthesis inhibitor. We cultured and treated plant materials using our newly developed methods, and observed the morphology of wild type ovules and fluorescence signals in a marker line to monitor the progress of ovule development. The results demonstrate BR promotes ovule development and our new methods are efficient and repeatable.